A Qualitative Analysis of the Effects of Depression and Antidepressants on Physical and Work Functioning among Antiretroviral Therapy Clients in Uganda. (November 2013) - Ngo, Victoria K.; Wagner, Glenn J.; Huynh, Alexis; Ryan, Gery; Musisi, Seggane
Depression is common among people living with HIV/AIDS in sub-Saharan Africa. Yet, little is known about how depression influences physical health and socioeconomic well-being in the context of antiretroviral therapy (ART). Semistructured interviews with 40 adult HIV clients receiving ART in Uganda were conducted to assess experiences prior to and after HIV diagnosis and initiation of ART. Content analysis revealed themes that were suggestive of the following patterns: (1) functioning decreased after patients were diagnosed with HIV, but improved following ART, (2) depression is associated with lower physical health functioning and work status levels after both HIV diagnosis and ART, and (3) antidepressant medication is associated with better functioning compared with patients with depression not receiving depression treatment. These findings suggest that depression plays a role in the deleterious effects of HIV on functioning, and that antidepressant treatment provided alongside ART may serve to help individuals regain functioning, particularly employment. These findings highlight the potential value of integrating depression treatment into HIV care.